2009
DOI: 10.1016/j.conbuildmat.2008.08.019
|View full text |Cite
|
Sign up to set email alerts
|

The effects of using lime and styrene–butadiene–styrene on moisture sensitivity resistance of hot mix asphalt

Abstract: This study focuses on determining the effects of styrene-butadiene-styrene (SBS) and using mineral filler with lime on various properties of hot mix asphalt especially moisture damage resistance. The asphalt cement was modified with 2%, 4% and 6% SBS. The lime treated mixtures containing 2% lime by weight of the total aggregate as filler. The physical and mechanical properties of polymer modified binder and binder-aggregate mixes were evaluated through their fundamental engineering properties such as dynamic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(62 citation statements)
references
References 10 publications
7
52
0
3
Order By: Relevance
“…The type of aggregate made some differences in TSR values of mixtures. The results also showed that Aspha-min additives make a cohesive failure in all cases [13].…”
Section: Moisture Susceptibility Of Wmasmentioning
confidence: 57%
See 2 more Smart Citations
“…The type of aggregate made some differences in TSR values of mixtures. The results also showed that Aspha-min additives make a cohesive failure in all cases [13].…”
Section: Moisture Susceptibility Of Wmasmentioning
confidence: 57%
“…The results showed that both of the modifiers improved stiffness, strength and stability of asphalt concrete. Also they reported that addition of only 2% lime have approximately same effect with addition of 6% SBS and mixtures containing both 2% lime and 6% SBS, have higher moisture resistance [13]. In other study by wei et.al (2017) on the effect of Diatomite and SBS on moisture sensitivity resistance of crumb rubber modified SMA, it has been shown that SBS modifier reduces air void and improve sensitivity moisture performance of these mixtures [14].…”
Section: Polymer Modificationmentioning
confidence: 84%
See 1 more Smart Citation
“…SBS, bitüm ile karıştırıldığında yağsı fraksiyonları bünyesine alarak hacmi artmaktadır. Bitüm modifikasyonunda en sık kullanılan polimer olan elastomer türü stirenbutadien-stiren (SBS) blok kopolimerlerinin, bitümün rijitliğini arttırmasının yanı sıra düşük servis sıcaklıklarında çatlama, yüksek servis sıcaklıklarında ise tekerlek izi oluşumu ve yorulmaya karşı dayanımı arttırdığı belirlenmiştir [10][11][12][13].…”
unclassified
“…It increases the elasticity of bitumen. It has been identified that SBS can obviously improve the mechanical properties of mixtures such as aging [9,10], permanent deformation [11][12][13][14][15][16][17], low temperature cracking [18][19][20] and moisture damage resistance [21][22][23].…”
Section: Introductionmentioning
confidence: 99%